Open-end winding induction machine fed by a dual-output indirect matrix converter - Riedmann, Javier; Clare, Jon C.; Wheeler, Patrick; Blasco Giménez, Ramón; Rivera, Marco; Pena, Ruben (Institute of Electrical and Electronics Engineers, 2016)
Open-ended winding induction machines fed from standard two-level Voltage Source Inverters (VSI) provide an attractive arrangement for AC drives. An alternative approach is to use a dual output Indirect Matrix Converter (IMC). It is well known that the IMC provides fully bidirectional power flow operation, with small input size filter requirements. Whilst a standard IMC consists of an AC-DC matrix converter input stage followed by a single VSI output stage, it is possible to replicate the VSI to produce multiple outputs. In this paper an open-end winding induction machine fed by an IMC with two output stages is presented. The IMC modulation strategy aims to reduce the common-mode voltage whilst compensating any zero sequence voltage fed to the machine. The system is modeled using a PSIM and MATLAB/Simulink platform. Experimental results demonstrating the viability of the method are presented using a 7.5 kW prototype.